Extreme Sports Medicine - Feletti, Francesco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This technically oriented book on medicine as applied to extreme sports offers broad coverage of the field extending well beyond the usual focus on major trauma and acute injuries. In addition to the injuries and diseases associated with individual extreme sports, this book also addresses the topics of psychology, dermatology, ophthalmology, infectious diseases, physiology, nutrition, training, injury prevention strategies, rehabilitation, doping, treatment in hostile environments, and legal aspects. Innovative and less frequently considered topics are also discussed, such as recent advances in protective equipment and materials, the effects of exposure on whole-body vibration, and cold exposure risk management. More than 60 of the most authoritative experts from across the world have contributed to this book, drawing on their personal experiences and including practical examples whenever relevant. Both subject matter and illustrations have been selected with the utmost care, the latter including photographs of world-class athletes.The book$1 (Bs multidisciplinary approach to the subject ensures that it will be relevant to a wide readership.s
Part I. Medicine in extreme sports: 1Psychology and the extreme sports experience -- 2 Nutrition for extreme sports -- 3 Endocrine responses to extreme sports -- 4 Infectious diseases and extreme sports -- 5 Ocular problems in extreme sports: high altitude trekking and surfing -- 6 Extreme sports dermatology -- 7 Medical support for expedition-length adventure races -- 8 Emergency medicine in mountain sports: treatment of casualties in hostile environments -- 9 Drug abuse and doping in extreme sports. Part II. Injuries and illnesses in the most popular extreme sports: 10 Rock and ice climbing medicine -- 11. Alpine skiing and snowboarding: current trends and future directions -- 12 Extreme mountain biking injuries -- 13 Ultramarathon running: medical issues -- 14Skateboarding: accidents and injuries -- 15 BASE jumping and wingsuit flying: accidents and injuries,- 16 Foot-launched flying: accidents and injuries. Hang gliding, paragliding, powered hang gliding and powered paragliding -- 17 Paragliding medicine -- 18 Kitesports medicine: Kite surfing, snow kiting and kite buggying -- 19 Injuries associated with skydiving -- 20 Surfing and skimboarding medicine -- 21 Windsurfing injuries -- 22 Extreme sailing injuries -- 23 White-water paddlesports medicine: canoeing, kayaking and rafting -- 24 Wakeboarding injuries. 25 Extreme scuba diving medicine. Part III. Prevention, training and rehabilitation: 26 Training and injury prevention strategies in extreme sports -- 27 An ecological dynamics framework for the acquisition of perceptual motor skills in climbing -- 28 Windsurfing: the physiology of athletic performance and training -- 29 Employment of near-infrared spectroscopy to assess the physiological determinants of hiking performance in single-handed dinghy sailors -- 30 Whole body vibration in extreme sports -- 31 Physiology and risk management of cold exposure -- 32 Helmets: technological innovations for safety -- 33 The eye in extreme sports: prevention, treatment and rehabilitation -- 34 Rehabilitation of extreme sports injuries -- 35 Legal issues related to extreme sports.
Keywords: Medicine; Orthopedics; Sports medicine; Medicine & Public Health; Sports medicine; Orthopedics